2021
DOI: 10.14710/jpk.8.2.109-115
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Factors of Using Public Transportation Among Women in Kuala Lumpur

Abstract: In recent decades, the percentage of women working outside their homes has ascended in many developing countries depicts the needs on the understanding of how women travel daily. Many claims, public transportation facilities, and infrastructure related to it do not consider the needs of women travelers but fit men's standards. As a result, many face difficulties became dependent on men for traveling or facing safety-related issues that deter them to use public transportation independently. Thus, this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The same also applies to women (Al-Rashid et al, 2020;Campisi et al, 2020;Harumain et al, 2021) and it is indicated in Table 3 by a hypothesized positive correlation between gender (i.e., male:1, female:2) and fear/stress/anxiety emotions. Car owners and drivers are also expected to be under lower levels of fear, stress, and anxiety since they are not public transport captive users and have alternative traveling options.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The same also applies to women (Al-Rashid et al, 2020;Campisi et al, 2020;Harumain et al, 2021) and it is indicated in Table 3 by a hypothesized positive correlation between gender (i.e., male:1, female:2) and fear/stress/anxiety emotions. Car owners and drivers are also expected to be under lower levels of fear, stress, and anxiety since they are not public transport captive users and have alternative traveling options.…”
Section: Discussionmentioning
confidence: 86%
“…Given the importance of these psychological stimulations during the COVID-19 pandemic phases and the emerging challenges, recent research has also considered the psychological perspective to analyze travel behavior. The psychosocial and situational aspects can influence modal choices, often becoming a real barrier resulting from various factors such as age (Al-Rashid et al, 2021) or gender (Al-Rashid et al,2020;Harumain et al, 2021). Transport demand from the early stages of the pandemic was also strongly influenced by these behavioral aspects (Anagnostopoulou et al, 2020;Borkowski et al,2021).…”
Section: Psychological Status Of Citizens and Possible Impact On Public Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…A large segment of older adults in the country remains deprived of socio-economic opportunities and cannot participate in socio-economic activities effectively [8]. They are socially excluded and face various disadvantages because they lack the travel means to address such concerns [9,10]. The physical activity levels and mobility of older adults in Pakistan are inadequate [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary at the same time to consider that by increasing densities in and around the compact city, public transport systems can no longer meet the dispersed pattern of the transport demands of all citizens [19,20]. Therefore, two alternatives should be referred to, namely the commonly used line-by-line approach and the integrated and nodal approach.…”
Section: Introductionmentioning
confidence: 99%